Patient safety in anesthesia in surgical procedures (Research, Society and Development, 2024)
Introduction: Anesthesia is an important factor that guarantees the safety of a surgical environment. Anesthetic practice has sought greater safety in performing procedures in recent years. Complications and reductions in the number of deaths caused by anesthesia have plummeted in recent decades. Objective: This research aims to highlight the importance of safety in anesthetic procedures in a surgical environment, as several complications can be avoided, reducing post-surgical morbidity and mortality. Methodology: This is a descriptive qualitative study, defined by an integrative literature review, it is a relevant instrument in communicating research results, as it provides a synthesis of the knowledge already produced and provides contributions to data production. Discussion: It is the anesthetist's responsibility to identify, treat and mainly prevent, in the perioperative period, all risk factors that could lead the patient to a complication related to the anesthetic procedure. The importance given to the anesthetic procedure involves incidents that can lead to the patient's death, disconnection of the respiratory circuit, exchange of syringes with medications, control of adequate oxygenation, and the lack of ideal ventilatory support, represent important factors linked to patient mobility. in surgery. Conclusion: This work does not seek to end discussions about the importance of pre-anesthetic consultation for surgical procedures, as it is of great importance that there be further publications and research in the search for validating the encouragement of protocols and conduct that guarantee patient safety. patient.